Diagnostics and therapy of peripheral neuropathy (literature review) - G. Y. Levina; Y. N. Bykov; A. S. Borisov (Acta Biomedica Scientifica)
The review is devoted to diagnostics and treatment of neuropathic pain in patients with peripheral nervous system diseases. Main assessment tools are shown including Visual analog Scale (VAS), Neuropathic Pain Scale (NPS), Leeds Assessment of Neuropathic Symptoms and Signs (LANSS), self-report version of the Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS), Neuropathic Pain Questionnaire (NPQ), Questionnaire Douleur Neuropathique 4 (DN-4), pain DETECT Questionnaire, Standardized Evaluation of Pain (StEP), identification pain questionnaire (ID-pain), clinical investigation (quantitative sensorial test are included), neurophysiological studies (electroneuromyography, evoked potentials) and MRI. Novel therapy in neuropathic pain disorders is described including both medicamentous and additional therapeutics methods.